Scaffolding as a teaching strategy to enhance mathematics learning in the classroom / Paul Lau Ngee Kiong ... [et al.] - Paul, Lau Ngee Kiong; Hwa, Tee Yong (2006)
This report presents the findings of a research study, entitled Scaffolding as a teaching strategy to enhance the teaching and learning of mathematics in the classroom, which examined ways in which the participating teachers learned to teach mathematics effectively using scaffolding and the different types of scaffolding interactions between teachers and students that were most productive for mathematics learning.